Succinate communicates pro-inflammatory signals to the host and regulates bile acid enterohepatic metabolism in a pig model. Issue 21 (5th October 2022) - Li, Xuan; Ren, Yuting; Huang, Guowen; Zhang, Ruofan; Zhang, Yanan; Zhu, Weiyun; Yu, Kaifan
Abstract : Pro-inflammatory cytokines induced by succinate blocked the activation of FXR and its target genes and disturbed bile acid enterohepatic circulation. Abstract : Succinate is produced by both the host and microbiota with pleiotropic functions in the modulation of intestinal inflammation and metabolic homeostasis, but the mechanisms remain elusive. This study aimed to determine whether dietary succinate influences the intestinal inflammatory response and to analyze the possible mechanisms by which succinate regulates enterohepatic metabolism. Sixteen growing barrows were randomly assigned to two groups, fed with a basal diet that consisted of a typical commercial diet or fed with a basal diet supplemented with 1% sodium succinate. Our data showed that dietary succinate activated the expression of succinate receptor 1 (SUCNR1) and increased the concentrations of pro-inflammatory cytokines in the intestine. Dietary succinate inhibited the expression levels of the ileal Farnesol X receptor (FXR) and its target genes, promoted hepatic bile acid secretion, and altered the bile acid metabolic profile. Then, we demonstrated that the pro-inflammatory cytokines triggered by succinate disrupted the ability of bile acids to activate FXR and fibroblast growth factor 19. Furthermore, dietary succinate reduced the abundance of bile-salt hydrolase enriched bacteria in the ileum. Taken together, dietary succinate activated the pro-inflammatory response via SUCNR1 in the intestine, and the pro-inflammatory cytokines induced by succinate blocked the activation of FXR and its target genes and disturbed bile acid enterohepatic circulation.